Effectiveness Of Shakehand Grip And Penhold Grip On Accuracy Of Backhand Services In Table Tennis Games - Rani Nopriati; Dedi Iskandar (Journal of Physical Education and Sport Science, 2019)
The research focuses on the effectiveness of using shakehand grip’s styleand penhold grip’s style on target accuracy in backhand service in JuniorHigh School 2 Cigugur. The aim of this research is to find out theeffecitiveness of using shakehand grip’s style and penhold grip’s style ontarget accuracy in backhand service in table tennis games. The researcherused the instrument about skill of table tennis test Tes Service to find outthe effectiveness of using shakehand grip’s style and penhold grip’s styleon target accuracy in backhand service. The research method is usingquantitative. One of the quantitative method which used in this reseacrchis expreiment method with using research design The One Group PretestPosttest Design. The researcher has been found that shakehand grip’sstyle is more effective than penhold grip’s style on target accuracy inbackhand service in table tennis games.it proved with significant score(increase) after giving some treatment. Shakehand grip’s style has beenincreased 12,04 while penhold grip’s style has been increased 5,48. Hypothesis test showed that score >was 3,99 > 1,743which means the hypothesis accepted. © 2019 STKIP